Pilot evaluation of a socio-emotional learning program on executive functions in elementary school students: a cluster-randomized controlled trial - Antunes, Rita; Carneiro, Tânia; Joaquim, Luciana; Matos, Margarida; Alexandre, Joana; Filipe, Marisa G. (Frontiers in Psychology, 2025)
Social and Emotional Learning (SEL) programs aim to enhance children’s socio-emotional competencies. While research has highlighted the positive socio-emotional outcomes of SEL programs, their transfer effects on executive functions remain unclear. This pilot cluster-randomized controlled trial explored the impact of a SEL program – The Intergalactic World – on executive functions in a cohort of first to fourth-graders. Participants were randomly assigned to either an intervention group (n = 60; 26 girls; Mage = 94.95 months, SD = 15.53), which participated in the SEL program, or to a waiting list control group (n = 36; 19 girls; Mage = 111.62 months, SD = 6.80). The SEL program comprised eight sessions conducted in a school setting to enhance socio-emotional development through breathing exercises, relaxation techniques, guided imagery, and cognitive-behavioral strategies. Executive functions were assessed for both groups using a standardized questionnaire, with evaluation conducted before and after the program implementation by teachers and caregivers. Pre- and post-intervention assessments revealed no significant changes in executive function scores based on teacher ratings across groups. In contrast, caregiver ratings of executive functions showed a significant interaction effect between time and group, with the intervention group exhibiting a positive change over time compared to the control group. Results yield valuable insights into the potential benefits of SEL interventions concerning elementary school students’ executive functions.